2020
DOI: 10.1101/2020.02.02.931022
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Loss of a conserved MAPK causes catastrophic failure in assembly of a specialized cilium-like structure inToxoplasma gondii

Abstract: TOC: Toxoplasma gondii that lack the kinase ERK7 cannot invade or egress from their host cells, thereby blocking their replicative cycle. These defects are due to the loss of a specialized cilium-like structure called the conoid. Strikingly, the ultrastructural changes are specific to the conoid, and suggest an important role for ERK7 in its biogenesis. AbstractPrimary cilia are important organizing centers that control diverse cellular processes. Apicomplexan parasites like Toxoplasma gondii have a specialize… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
40
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 14 publications
(46 citation statements)
references
References 36 publications
5
40
1
Order By: Relevance
“…Usually, genetic ablation of an inhibitor would be expected to present the opposite phenotype from its target. Because ERK7 kinase activity is required for conoid formation (17), our data suggest that AC9 inhibition of the kinase is not permanent. Instead, we propose that AC9 binding to ERK7 represents an unusual mechanism of ensuring kinase specificity ( Figure 6D).…”
Section: Discussionmentioning
confidence: 78%
See 4 more Smart Citations
“…Usually, genetic ablation of an inhibitor would be expected to present the opposite phenotype from its target. Because ERK7 kinase activity is required for conoid formation (17), our data suggest that AC9 inhibition of the kinase is not permanent. Instead, we propose that AC9 binding to ERK7 represents an unusual mechanism of ensuring kinase specificity ( Figure 6D).…”
Section: Discussionmentioning
confidence: 78%
“…We recently demonstrated that ERK7 localizes to the apical cap, and that its loss-of-function phenotype is essentially identical to what we have observed for AC9 (17). We therefore prioritized investigating the function of this interaction.…”
Section: Proximity Biotinylation Reveals Ac9 Interacts With the Map Kmentioning
confidence: 74%
See 3 more Smart Citations